Issues and challenges among young entrepreneurs in Malaysia / Alia Nabilah Ahmad Puad - Ahmad Puad, Alia Nabilah (2020)
For this assignment, it is about reviewing an article related to entrepreneurship. I choose an article title “Issues and Challenges among Young Entrepreneurs in Malaysia” by the Journal of Business and Management. The article is about the involvement of young entrepreneurs has increase year by year since 2014. However, the percentage of failures among young entrepreneurs is higher than the successful entrepreneur. There are so many issues and challenges for the entrepreneur to survive in the industry. But, with a thorough understanding of entrepreneurship and business industry will help them to improve. The reason why I chose this article because becoming self-employed is not easy because they must have knowledge and strength both mentally and physically. Youth cannot rely on job opportunities because more job will become irrelevant as the technology developed rapidly. So, being an entrepreneur is one of the ways that will help them in future. However, there are so many challenges to become a successful entrepreneur. In the article, it stated that there is only 20 percent of young entrepreneur are successful and survive in the industry. So, future entrepreneurs must alert with the current issues and the challenges of becoming a successful entrepreneur and get prepared physically and mentally.